Influence of functional group of dye on the adsorption behaviour of CoFe2O4 nano-hollow spheres. (28th July 2017) - Rakshit, Rupali; Khatun, Esma; Pal, Monalisa; Talukdar, Souvanik; Mandal, Dipika; Saha, Priyanka; Mandal, Kalyan
Abstract : Excellent preferential dye adsorption of CoFe2 O4 nano-hollow spheres. Abstract : Herein, we report the origin of excellent dye adsorption behaviour of CoFe2 O4 nano-hollow spheres (NHSs) which are synthesised by a facile template free solvothermal technique and we investigate the influence of different anionic functional groups of the dyes on their adsorption rate. It is found that CoFe2 O4 NHSs of diameter 250 nm adsorb a total 95% of fluorescein, 32% of bromophenol blue, and 15% of bromocresol green dyes within only 2 min and reach equilibrium in about 4, 6, and 10 min, respectively. Detailed study through UV-visible and Fourier transformed infra-red spectroscopies reveals that these magnetic adsorbents show highly efficient adsorption performance due to their high surface area, porous nature, and surface complexation with the dyes through strong electrostatic and hydrogen bonding. The variation in adsorption rate of CoFe2 O4 NHSs for three different dyes indicates that the electron density of the anionic functional group and the steric effect of the dye molecule play a key role in determining the adsorption rate. The adsorption kinetics and isotherms of the adsorbents are found to follow pseudo 1st order kinetics and the Freundlich isotherm, respectively, implying heterogeneous physisorption of the dyes over the NHS surface. Moreover, the amount of dye adsorbed on the surface of NHSs is found to increase with increasing size of the NHSs and initial dye concentration. Finally, CoFe2 O4 NHSs can be regenerated through desorption of dyes at higher pH and still exhibit high adsorption capacity even for 5 cycles of desorption–adsorption.